CAND2/PMTR1 Is Required for Melatonin-Conferred Osmotic Stress Tolerance in Arabidopsis - Wang, Lin-Feng (Int J Mol Sci, 2021)
Osmotic stress severely inhibits plant growth and development, causing huge loss of crop quality and quantity worldwide. Melatonin is an important signaling molecule that generally confers plant increased tolerance to various environmental stresses, however, whether and how melatonin participates in plant osmotic stress response remain elusive. Here, we report that melatonin enhances plant osmotic stress tolerance through increasing ROS-scavenging ability, and melatonin receptor CAND2 plays a key role in melatonin-mediated plant response to osmotic stress. Upon osmotic stress treatment, the expression of melatonin biosynthetic genes including SNAT1, COMT1, and ASMT1 and the accumulation of melatonin are increased in the wild-type plants. The snat1 mutant is defective in osmotic stress-induced melatonin accumulation and thus sensitive to osmotic stress, while exogenous melatonin enhances the tolerance of the wild-type plant and rescues the sensitivity of the snat1 mutant to osmotic stress by upregulating the expression and activity of catalase and superoxide dismutase to repress H(2)O(2) accumulation. Further study showed that the melatonin receptor mutant cand2 exhibits reduced osmotic stress tolerance with increased ROS accumulation, but exogenous melatonin cannot revert its osmotic stress phenotype. Together, our study reveals that CADN2 functions necessarily in melatonin-conferred osmotic stress tolerance by activating ROS-scavenging ability in Arabidopsis.